EFEKTIVITAS MODEL PEMBELAJARAN INSETS BERBASIS KEARIFAN LOKAL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X SMA DHARMA AYU - Finsensius Oetpah; Lusia Naimnule (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to integrate a valid, practical, and effective local wisdom-based science learning model (INSETS) so that it is feasible to improve the critical thinking skills of high school students. The research design uses a development research design with a one-group pretest-posttest design. The subjects in the limited trial were conducted in class X at SMA Dharma Ayu, consisting of 19 students. The data collection process was carried out through documentation, tests, and questionnaires. The data analysis techniques used were quantitative and qualitative descriptive, n-gain, and paired t-test. The research results indicate: (1) the content validity of the INSETS learning model meets the criteria of very valid, (2) the consistency of the construct validity of the INSETS learning model meets the criteria of very valid, (3) the implementation stages of the INSETS learning model in limited and extensive trials fall within the good and fairly good criteria, and (4) students' critical thinking skills in limited trials and widespread tests increased significantly. It is concluded that the INSETS learning model developed is feasible to be used to effectively improve the critical thinking skills of students at SMA Dharma Ayu Kefamenanu. The results of the pretest and posttest trials were normally distributed and homogeneous. The paired t-test results showed that the significance level was < 0.05. This means that the INSETS learning model based on local wisdom is effective in improving the critical thinking skills of tenth-grade students at SMA Dharma Ayu.